2003
DOI: 10.2355/isijinternational.43.386
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of High-temperature Oxidation Resistance for Ni-based Alloys by Re Addition and the Optimization of Re/Al Content.

Abstract: High-temperature oxidation tests were conducted with two groups of Ni-based superalloys in order to elucidate the Re effect on oxidation resistance. One group of alloys was the Ni-8Cr-2Ti-10Al-Re system, characterized by 10 mol% Al content. The other group of alloys was the Ni-8Cr-2Ti-15Al-Re system, characterized by 15 mol% Al content. The alloy compositions were chosen with the aid of the d-electrons concept, so that any undesirable phases would not appear in the microstructure. Both cyclic and isothermal ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…17 Isothermal tests carried out at 1,100°C showed that the oxidation resistance decreased with increasing rhenium content in the 5Al series of alloys, but did not do so in the 7.7Al series. It was concluded that the Re/Al ratio may be an indicator of oxidation resistance in superalloys.…”
Section: The Effect Of Alloying On the Oxidation Of Nickel-based Allomentioning
confidence: 96%
See 1 more Smart Citation
“…17 Isothermal tests carried out at 1,100°C showed that the oxidation resistance decreased with increasing rhenium content in the 5Al series of alloys, but did not do so in the 7.7Al series. It was concluded that the Re/Al ratio may be an indicator of oxidation resistance in superalloys.…”
Section: The Effect Of Alloying On the Oxidation Of Nickel-based Allomentioning
confidence: 96%
“…16,17 Giggins and Pettit investigated the ternary Ni-Cr-Al alloys, including a binary Ni-5Cr and another Ni-3Al alloy. 16, Isothermal oxidation, carried out at temperatures between 1,000°C and 1,200°C, showed that after a brief initial transition period the mass gain remained parabolic with respect to time, and the oxidation rate of each alloy increased with an increase in temperature.…”
Section: The Effect Of Alloying On the Oxidation Of Nickel-based Allomentioning
confidence: 99%
“…[7] Of note here is the oxidation of the third-generation superalloy RENÈ N6. In another recent investigation, the Re content was varied in Ni-8Cr-2Ti-10Al-Re and Ni-8Cr-2Ti-15Al-Re alloys [15] (the concentrations expressed in atomic percent), and it was found that alloys with a Re/Al ratio of 0.1 exhibited only a small mass change, which resulted from oxidation. [14] It was found that reducing the sulfur content to a level below 0.1 ppm prevented spalling of the scale, which results from thermal cycling.…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study the Al/Re ratio in this family of superalloys has been suggested as an indicator for the degree of oxidation resistance. 7 One would therefore expect the oxide scale to vary significantly between the second and third generations of single crystal superalloys, where the Re and Al concentration varies notably and this has indeed been shown to be the case. The structure and composition of the oxide scale that forms on bare CMSX-10, a third generation nickel based blade alloy, has been studied by Akhtar et al 3 and Younes et al 8 showing the formation of an external layer made of Ni, Co oxide atop an internal oxidation zone comprised of Ni, Co, Al, Cr, Ta and W rich spinels.…”
Section: Introductionmentioning
confidence: 96%